2012
DOI: 10.4046/trd.2012.73.5.258
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Vitamin D Receptor Translocation by Cigarette Smoking Extracts

Abstract: BackgroundVitamin D can translocate a vitamin D receptor (VDR) from the nucleus to the cell membranes. The meaning of this translocation is not elucidated in terms of a role in pathogenesis of chronic obstructive pulmonary disease (COPD) till now. VDR deficient mice are prone to develop emphysema, suggesting that abnormal function of VDR might influence a generation of COPD. The blood levels of vitamin D have known to be well correlated with that of lung function in patients with COPD, and smoking is the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 22 publications
1
22
1
Order By: Relevance
“…(P=0.105) Similar to Syal SK study which is an Indian study. 21 This variation may be due to ethnic differences as observed by Sragg R. 25 As cigarette smoking inhibits Vitamin D induced translocation of VDR from the nucleus to the cell membrane efficiency of Vitamin D decreases as observed by Uh ST et al 16 Though Brot C observed deleterious effect of smoking on Vitamin D level, our study did not show any significant correlation between Smoking and Vitamin D level. 26 Significant link between family history (an important nonmodifiable risk factor) of CAD and Vitamin D level was observed by Entezari-Maleki, Taher.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…(P=0.105) Similar to Syal SK study which is an Indian study. 21 This variation may be due to ethnic differences as observed by Sragg R. 25 As cigarette smoking inhibits Vitamin D induced translocation of VDR from the nucleus to the cell membrane efficiency of Vitamin D decreases as observed by Uh ST et al 16 Though Brot C observed deleterious effect of smoking on Vitamin D level, our study did not show any significant correlation between Smoking and Vitamin D level. 26 Significant link between family history (an important nonmodifiable risk factor) of CAD and Vitamin D level was observed by Entezari-Maleki, Taher.…”
Section: Discussioncontrasting
confidence: 53%
“…14 Ford ES demonstrated inverse relationship of vitamin D level with MS. 15 Smoking causes decrease in Nitric Oxide (NO) availability and inhibits translocation of vitamin D receptor from the nucleus to the cell membrane resulting in VDD. 16 Cardio vascular diseases (CVD) specially CAD has shown a steep rise in last few decades in India due to rising trend of obesity, high blood pressure, dyslipidemia, change in food habits ,sedentary life style. New emerging risk factors like VDD homocysteine level and inflammation are under recent investigations.…”
Section: Introductionmentioning
confidence: 99%
“…The actions of the vitamin D hormone [1,25‐dihydroxyvitamin D 3 (1,25(OH) 2 D 3 )] are mediated by the nuclear VDR, which when activated, causes transcription of several genes which regulate calcium metabolism and expression of cytokines and key antimicrobial peptides (Pike & Meyer, ). Cigarette smoking extracts interfere with the binding of vitamin D to its receptors and inhibit VDR translocation from the nucleus to the cytoplasm with subsequent impairment in the intracellular signaling pathway (Uh et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…One study has shown that exposing cells in culture to cigarette smoke inhibits vitamin D induced translocation of the nuclear VDR [73], however this appears to be the only evidence that cigarette smoke has a direct impact on vitamin D pathways. While acknowledging that work in this area is limited the potential upregulation of VDR in response to an insult has important implications when considering the validity of measuring 25(OH)D alone when examining disease associations.…”
Section: Chronic Obstructive Pulmonary Disease (Copd)mentioning
confidence: 99%